The Needle in the Haystack: Uncovering the First Whale Shark (Rhincodon typus) Aggregation in the Coral Sea - Ingo B. Miller; Richard Fitzpatrick; Kátya G. Abrantes; Bradley Norman; Simon J. Pierce; Mark V. Erdmann; Lisa A. Hoopes; Christine Dudgeon; Matthew D. Dunbabin; Alistair D. M. Dove; Robin J. Beaman; Samantha D. Reynolds; et al. (Ecology and Evolution, 2025)
ABSTRACT Aggregations are key events, supporting critical ecological and biological functions in many species. For highly mobile and elusive species, aggregations often provide the only feasible opportunities for research. Whale sharks (Rhincodon typus) form at least 30 consistent seasonal aggregation sites globally, yet none have been documented in the Coral Sea, despite sporadic sightings of solitary individuals and groups. This study aimed to identify and characterise the first whale shark aggregation on Australia's east coast by predicting potential sites through a data layering approach and confirming their presence through targeted field expeditions. A combination of historical sightings data, expert and anecdotal knowledge, and scientific knowledge from other whale shark aggregation sites led to the identification of Wreck Bay, situated at the far northern Great Barrier Reef, as potential aggregation habitat. An initial field expedition in 2019 confirmed the aggregation, and three subsequent voyages in 2021–2024 gathered further demographic and movement data. A total of 59 individuals were identified, with a strong male bias (3.5:1) and all classified as immature sharks ranging from 3.5 to 8.0 m in estimated total length. Satellite tracking revealed a mean residence time of approximately 3 weeks (21.6 days ±10.1 SD; range: 7–43 days), with some individuals revisiting the aggregation in subsequent years. The peak aggregation period occurs from late November to late December, with movements concentrated along the continental shelf before dispersing into the Coral Sea. Tracked sharks (n = 18) exhibited wide‐ranging movements, with a mean track duration of 144 days (range: 3–770 days) and a mean total track length of 1463 km (range: 19–11,355 km). This study provides the first evidence of a whale shark aggregation in the Coral Sea and highlights Wreck Bay as key habitat for this iconic and globally endangered species.